A LITERATURE SURVEY AND BIBLIOMETRIC ANALYSIS OF THE IMPACT OF CONTROLLING SHAREHOLDERS ON DIVIDEND POLICY - Geeta Singh; Kaushik Bhattacharjee; Srikanth Potharla (Copernican Journal of Finance & Accounting, 2023)
We conduct a systemic review of literature on whether controlling shareholders influence firms’ dividend polices. We examine the literature on the linear and non-linear association between the equity holding of the controlling shareholders and dividend policy. The review suggests lack of consensus on the role of insiders and controlling shareholders in deciding the firm’s propensity and intensity to pay dividends. Finally, we conduct a bibliometric analysis of the research articles referred in this study which suggests that the USA contributes most of the articles examining the dividend policy taking into consideration the ownership structure, with University of Chicago being the most relevant affiliation of the authors examining this relation.